Redes alimentarias alternativas de Medellín y el Oriente de Antioquia : espacios de construcción de confianza (2019)
ABSTRACT: Food supply in cities is largely managed by multinational companies using widespread systems, promoting the use of agrochemicals in food production, and generating unfair pricing and access. These factors have led to the creation of an alternative sector highlighting new mechanisms of production, distribution, and consumption of foods. Objective: Describe the principle characteristics of alternative food networks in Medellin and the eastern sub-region of the state of Antioquia, highlighting the actors, processes, and relationships among producers, distributors, and consumers of said food products. Materials and Methods: Qualitative collective case study in which the participants were selected for interviews given their ties to 15 alternative food networks and systems. Semi-structured interviews were conducted, as well as active observation in distribution areas and passive observation in production zones. Results: The basis for healthy food systems was found in these alternative initiatives, which are based on agro-ecology, fair trade, and healthy consumption and consumerism. When analyzed from the theoretical constructs of social capital, it’s seen that these networks help build ties between producers and consumers, and reinforce the bonds between the first links of these systems; however, stronger positioning is needed to strengthen these association. Conclusions: The recent advent of alternative food systems represents an opportunity to consolidate food sectors that contribute to the generation of social capital for the collective good of the population.